2010
DOI: 10.1126/scitranslmed.3001143
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Promotes Hepatitis B Virus–Induced Hepatocarcinogenesis Through Modulation of Hepatitis B Virus RNA Transcription

Abstract: Hepatitis B virus (HBV)-induced hepatitis and carcinogen-induced hepatocellular carcinoma (HCC) are associated with serum androgen concentration. However, how androgen or the androgen receptor (AR) contributes to HBV-induced hepatocarcinogenesis remains unclear. We found that hepatic AR promotes HBV-induced hepatocarcinogenesis in HBV transgenic mice that lack AR only in the liver hepatocytes (HBV-L-AR −/y ). HBV-L-AR −/y mice that received a low dose of the carcinogen N′-N′-diethylnitrosamine (DEN) have a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
162
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 43 publications
7
162
0
Order By: Relevance
“…Another study, which stably transfected functional AR into AR-negative HCC cells, revealed that cell growth was increased in the absence of androgen (46). These observations indicate that non-androgen-mediated AR signals may also be involved in hepatocarcinogenesis.…”
Section: Non-androgen-mediated Ar Signals In Hepatocarcinogenesismentioning
confidence: 86%
See 1 more Smart Citation
“…Another study, which stably transfected functional AR into AR-negative HCC cells, revealed that cell growth was increased in the absence of androgen (46). These observations indicate that non-androgen-mediated AR signals may also be involved in hepatocarcinogenesis.…”
Section: Non-androgen-mediated Ar Signals In Hepatocarcinogenesismentioning
confidence: 86%
“…This observation confirms the importance of androgen and AR in the mediation of HBV replication. A study by Wu et al (46) indicated that an aberrant overexpression of AR in HCC cells cooperates with HBV to enhance cell growth and invasion in vitro, and initiate HCC in vivo. Further studies have demonstrated that HBx, a HBV-encoded protein required for efficient viral replication, enhanced the gene transactivation activity of AR in the presence of androgens (38,39).…”
Section: Ar and Hbvmentioning
confidence: 99%
“…HBx enhances the AR transcriptional activity through two kinases: c-Src and glycogen synthase kinase-3beta kinase [51]. AR promotes HBV-induced hepatocarcinogenesis through modulation of HBV RNA transcription [52]. The androgen pathway can increase the transcription of HBV through direct binding to the ARE sites in HBV enhancer I, leading to a higher HBV titer in male carriers and increased risk of HCC [53].…”
Section: Androgen Receptor-mediating Signaling In Hbvrelated Hepatocamentioning
confidence: 99%
“…Incidental Wndings in each were that healthy volunteer HBV carriers had higher testosterone (T) concentrations than healthy uninfected volunteer controls (P = 0.045 and P = 0.0006, respectively, both two-way). The reason for this is not established and not directly relevant to the present note (though it may relate to variation in rates of viral replication in diVerent hormonal environments, if we may be guided by mouse models [4][5][6]). …”
mentioning
confidence: 91%